2016
DOI: 10.1139/gen-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Tube Barcoding

Abstract: Abstract:Here, we present a new approach for increasing the rate and lowering the cost of identifying, cataloging, and monitoring global biodiversity. These advances, which we call Closed-Tube Barcoding, are one application of a suite of proven PCR-based technologies invented in our laboratory. Closed-Tube Barcoding builds on and aims to enhance the profoundly important efforts of the International Barcode of Life initiative. Closed-Tube Barcoding promises to be particularly useful when large numbers of small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…2), which may or may not be contaminated by SN 2014C. To aid the comparison, the HST nativefilter magnitudes in the optical broad bands have been converted to the standard Johnson-Cousins system (F438W and F475X to the B band, F555W to the V band, and F814W to the I band) based on transformation relations reported by Sirianni, et al (2005) and Harris (2018). The UVband and narrow-band magnitudes are kept unchanged as in their native filters.…”
Section: Was the Sn Still Bright?mentioning
confidence: 99%
“…2), which may or may not be contaminated by SN 2014C. To aid the comparison, the HST nativefilter magnitudes in the optical broad bands have been converted to the standard Johnson-Cousins system (F438W and F475X to the B band, F555W to the V band, and F814W to the I band) based on transformation relations reported by Sirianni, et al (2005) and Harris (2018). The UVband and narrow-band magnitudes are kept unchanged as in their native filters.…”
Section: Was the Sn Still Bright?mentioning
confidence: 99%
“…Whilst it has been known that the COI gene is more slowly evolving in chondrichthyans than teleosts (Moore et al, 2011; Naylor et al, 2012), this is seldom a major issue in most DNA barcoding applications (Fields et al, 2018; Griffiths et al, 2013; Hobbs et al, 2019), so an optimised iteration of the FASTFISH-ID ™ method is poised to be transformational for elasmobranch conservation and management. A qualitative investigation on the full length of COI sequences (Sanger sequencing results) based on visual and simple comparison (https://www.bioinformatics.org/sms2/ident_sim.html) revealed that for those problematic three pairs of species mentioned above for that particular segment, there is a high degree of similarity in their sequence (70-98%), although this seems unlikely as the method is extremely sensitive and easily distinguishes between sequences that differ by a single nucleotide (Sirianni et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Sirianni et al (2016) outline their unique method termed Closed-Tube Barcoding, which may provide a rapid, affordable alternative to sequencing, especially for projects involving numerous samples. This approach also could be a step towards developing a portable barcoding device, with diverse applications such as monitoring mosquito populations.…”
Section: Advances In Quantificationmentioning
confidence: 99%